Neurobiology and Therapeutic Potential of α5-GABA Type A Receptors - Jacob, Tija C. (Frontiers in Molecular Neuroscience, 2019)
α5 subunit containing GABA type A receptors (GABAARs) have long been an enigmatic receptor subtype of interest due to their specific brain distribution, unusual surface localization and key role in synaptic plasticity, cognition and memory. These receptors are uniquely positioned to sculpt both the developing and mature hippocampal circuitry due to high overall expression and a distinct peak during the critical synapse formation period during the second postnatal week. Unlike the majority of other GABAARs, they exhibit both receptor clustering at extrasynaptic sites via interactions with the radixin scaffold as well as synaptic sites via gephyrin, thus contributing respectively to tonic currents and synaptic GABAergic neurotransmission. α5 GABAAR signaling can be altered in neurodevelopmental disorders including autism and mental retardation and by inflammation in CNS injury and disease. Due to the unique physiology and pharmacology of α5 GABAARs, drugs targeting these receptors are being developed and tested as treatments for neurodevelopmental disorders, depression, schizophrenia, and mild cognitive impairment. This review focuses on advances in understanding how the α5 subunit contributes to GABAAR neurobiology. In particular I discuss both recent insights and remaining knowledge gaps for the functional role of these receptors, pathologies associated with α5 GABAAR dysfunction, and the effects and potential therapeutic uses of α5 receptor subtype targeted drugs.